Auxiliar de educador(a) no ensino fundamental: desafios da profissão no contexto da Educação Inclusiva - Gallo, Débora Regina (Universidade Estadual de Ponta Grossa (UEPG), 2026)
This study is linked to the research line “Practices and Formative Processes of Educators for Inclusive Education” of the National Network Professional Master’s Program in Inclusive Education (PROFEI) and to the Study and Research Group on Learning Processes (GEP-ProA). The object of this research is the work of school support professionals, referred to in the city where the study was conducted as teacher assistants. The general objective of this research is to understand the work and challenges faced by teacher assistants in regular classrooms from the 1st to the 9th grade of elementary education. The specific objectives are: to characterize the sociodemographic and professional profile of these professionals; to identify possibilities and limits in their professional practice; and to collaboratively design an educational resource. As methodological procedures, a Google Forms questionnaire was applied to collect data on the participants’ sociodemographic and professional profiles, addressing issues such as age, gender, race, initial and continuing education, and work experience. The sample consisted of 11 participants, ten women and one man, working as teacher assistants in a municipal school located in northern Santa Catarina, Brazil. In addition, two in-person focus group meetings were held with these professionals, guided by a semi-structured script addressing the challenges encountered in their professional practice, as well as their demands and expectations. Authors such as Vygotsky (2021), Kassar (2011), Ferracioli (2022), Mészáros (1930), Saviani (2007), and Januzzi (2004) provided the theoretical basis for the research and data analysis. The main results revealed a lack of legislation supporting the profession, multiple work demands, and limited opportunities for continuing education, highlighting the undervaluation of these workers.
Keywords: Educação Inclusiva; Auxiliar de professor(a); Registro pedagógico